ANALISIS EKSPRESI ANAK USIA 3 TAHUN DALAM MENGUNGKAPKAN EMOSI - Rahmadani, Destri Yanti; Arianti, Rita (Jurnal Ilmu Pendidikan Ahlussunnah, 2025)
This study aims to describe eight types of emotions in children based on Goleman’s theory : anger, sadness, fear, enjoyment, love, surprise, shame. The research employs a qualitative approach with a descriptive method. Data were collected through voice recodings of the child’s verbal expressions and analyzed comprehensively. The findings indicate that the child’s verbal expressions are influenced by specific situations, social interactions, parenting styles and the surrounding environment. The child expresses emotions through speech patterns such as tone, intonation, and word repetition. Fear was identified as the most frequently expressed emotion, while enjoyment was the least expressed. This study highlights the crucial role of parents and caregivers in helping children manage their emotions through emotional support and a conducive environment. By understanding how children express their emotions, parents can more effectively guide them in managing their feelings positively, ultimately fostering emotional development within diverse cultural contexts.